Unpacking Soft Radicalism among Indonesian State Islamic University Students - Rahman, Fazlul; Mala, Faiqotul (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Radicalism remains a significant threat to global security, manifesting in various forms, including violent and non-violent approaches. In Indonesia, soft-radicalism—a non-violent form of radicalism that subtly spreads extremist ideologies through digital platforms—poses a growing threat, particularly among Muslim students at State Islamic Universities (PTKIN). This study examines the experiences, views, and attitudes of Muslim students toward soft radicalism, focusing on their exposure to radical content on social media. Through interviews and focus group discussions, the study reveals that students frequently encounter provocative content that challenges state legitimacy and promotes alternative socio-political systems like the caliphate. While students display critical awareness of these narratives, the persistent exposure facilitated by social media algorithms underscores the need for “inclusive digital navigation skills” for them. The skills to wisely and critically navigate the digital world, filter out potentially damaging information and interact in positive, inclusive, and respectful ways of diversity.